Statines and increased risk of diabetes mellitus de novo. what are its practical implications in the clinic? - Chicangana Tuquerres, Diver Alexis; Torres Perez, Paula Andrea; Bastidas Erazo , Ana María; Figueroa Torregroza, Lunevar; Feriz Bonelo, Karen Milena; Casanova Valderrama, María Eugenia (Interdisciplinary Journal of Epidemiology and Public Health, 2023)
Background: Cardiovascular disease is the leading cause of death in the world and in Colombia. Statins, as a pharmacological group, are considered first-line therapy, both in primary and secondary prevention, to reduce major cardiovascular outcomes. However, since the increase in cases of Diabetes mellitus 2 was reported in the population consuming statins, entities such as the FDA added a warning regarding their prescription, which meant a new evaluation of their risk-benefit ratio.Objective:  To determine the evidence related to the incidence of DM2 and the use of statins, contrasting with the efficacy of these drugs and to weigh their current use in clinical practice.Methods: A search was carried out in PubMED, SciELO and Elsevier, considering as selection criteria studies published between 2017-2022 and those considered "pivotal" or "transcendental", including 20 studies in total (10 clinical trials, 9 meta-analysis and 1 cohort study).Results:  Despite contradictory data, for some drugs in particular there was a greater strength of association (eg, Rosuvastatin and Atorvastatin), in a dose-dependent relationship. However, statins have a favorable risk-benefit balance, with a number needed to treat of 18-83 vs number needed to harm of 165-263, highlighting the lack of evidence in the Latin population.Conclusiones: The available evidence is in favor of the use of statins. In addition, the management of the patient with DM2, from the integral perspective of cardiovascular risk and without discriminating its etiology, includes the use of statins.